Collaborative governance in heritage tourism management: lessons from Lasem, Indonesia - Asmarani Februandari; Hermawan Prasetyanto (PHINISI, 2026)
This study examines how collaborative governance operates in heritage tourism management in Lasem, Indonesia, a historically layered town shaped by multicultural interactions and the marginalization of Chinese Indonesian heritage. Using a qualitative ethnographic approach, data were collected through participant observation during heritage walking tours, in-depth interviews, house and temple visits, and document analysis involving tourism awareness groups, heritage communities, homeowners, religious caretakers, and local officials. The findings reveal that heritage tourism in Lasem is governed through informal and practice-based collaboration embedded in everyday spaces. Collaborative governance enables the co-production of tourism activities, heritage narratives, and spatial access through negotiated roles and situational consent. However, collaboration is uneven, as tourism organizers and guides exercise greater influence over site selection and narrative framing, while local actors participate selectively in granting access and sharing personal histories. Heritage narratives tend to emphasize coexistence and hybridity, while politically sensitive histories are carefully moderated. This study contributes to collaborative governance theory by demonstrating that governance in socially sensitive heritage contexts operates through negotiated role differentiation rather than deliberative equality, highlighting the role of informal practices, selective participation, and power asymmetries in sustaining socially embedded tourism systems.